(untitled) (Heritage, 2022)
Tourism is very important for the development of the country. In order to develop, every country must invest in tourism and use its resources to attract tourists. This research took into account how natural and cultural resources influence the improvement of tourism performance. On that occasion, it was observed what influence the rate of economic growth has on the relationship between natural and cultural resources and the performance of tourism. Therefore, regression analysis was used with the mediator gross social product, which represents economic growth. The results showed that three out of four tourism performances are influenced by natural and cultural resources when changing the rate of economic growth. In this way, it has been proven that natural and cultural resources influence the performance of tourism. That is why tourism must be based on the natural and cultural resources available to the country. It is necessary to invest in infrastructure, especially in road infrastructure, in order to make these resources more accessible to tourists.